2008
DOI: 10.1080/15378020801926791
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Brand Attitude, Customers' Satisfaction and Revisiting Intentions of the University Students–A Case Study of Coffee Chain Stores in Taiwan

Abstract: The purpose of this research study was to investigate brand attitudes, which are associated with customer satisfaction, and the relationships between brand attitude, consumer satisfaction, and revisiting intentions of university students to coffee chain stores situated in the areas adjacent to universities. The purpose behind doing so was to provide appropriate marketing plan suggestions to the stores. The dimensions pertaining to brand attitude included cognitive, affective and conative components. The affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 33 publications
(26 reference statements)
0
14
0
2
Order By: Relevance
“…On the basis of these theoretical foundations and empirical evidences, it is reasonable to expect the significant impact of travelers' well-being perceptions on customer responses towards brand and behavior in the context of a duty free shop: Percy and Rossiter [82] conceptualized brand attitude in that motive-anchored and stressed brand attitude involves an expected buying motive. Brand attitude indicates customers' favorable or unfavorable responses that serve as an antecedent to customers' behavior, such as willingness to purchase and loyalty [83,84]. As the correlation between attitude and affect was found in social psychology, brand attitude was verified as a predictor of brand preference.…”
Section: Hypothesis 4 (H4) Travelers' Usability Experience Has a Posmentioning
confidence: 94%
“…On the basis of these theoretical foundations and empirical evidences, it is reasonable to expect the significant impact of travelers' well-being perceptions on customer responses towards brand and behavior in the context of a duty free shop: Percy and Rossiter [82] conceptualized brand attitude in that motive-anchored and stressed brand attitude involves an expected buying motive. Brand attitude indicates customers' favorable or unfavorable responses that serve as an antecedent to customers' behavior, such as willingness to purchase and loyalty [83,84]. As the correlation between attitude and affect was found in social psychology, brand attitude was verified as a predictor of brand preference.…”
Section: Hypothesis 4 (H4) Travelers' Usability Experience Has a Posmentioning
confidence: 94%
“…Hsu and Hung () suggest that the literature lacks information concerning the consumption of coffee at an age when coffee‐drinking habits are formed. Ko and Chiu () suggest that studying the consumption patterns of young adult coffee consumers could provide information about the consumer market. It is thus suggested that speciality coffee consumption is related to demographic factors.…”
Section: Theoretical Basis and Hypothesis Developmentmentioning
confidence: 99%
“…In other words, firm has to figure out the marketing strategy based to understand consumer attention. Based on the results of research by (Ko & Chiu, 2008), in the context of coffee shop consumers, attitude is an antecedent of customer satisfaction. Mohsin Butt & Aftab (2013) find significant relationship between attitudes toward halal banking toward consumer satisfaction in using online banking service in Pakistan.…”
Section: Hypothesis Development Attitude Toward Islamic Financial Technology and Consumer Satisfactionmentioning
confidence: 99%